2016
DOI: 10.1016/j.agrformet.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and abiotic controls in determining exceedingly variable responses of ecosystem functions to extreme seasonal precipitation in a mesophytic alpine grassland

Abstract: a b s t r a c tAs a result of global climate change, frequent and intensive extreme climate events are observed and predicted. These extreme climate events can change ecosystem functions through driving plant growth and mortality, as well as ecological and evolutionary processes into different directions. We simulated a 1-in-100-year extreme precipitation event in different plant growth seasons (i.e. spring, summer, or autumn) to investigate the functional responses of a mesophytic alpine grassland ecosystem t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…In China, a significant increase in extreme precipitation has occurred in the west, in the mid–lower reaches of the Yangtze River, and in parts of the southwest2. The changes in precipitation regimes will be more spatially heterogeneous and less predictable than other climate changes and will leads to more intense flooding occur at local and regional scales3. Scientists have been committed to ecosystem properties to stabilize and increase community stability under climate change45.…”
mentioning
confidence: 99%
“…In China, a significant increase in extreme precipitation has occurred in the west, in the mid–lower reaches of the Yangtze River, and in parts of the southwest2. The changes in precipitation regimes will be more spatially heterogeneous and less predictable than other climate changes and will leads to more intense flooding occur at local and regional scales3. Scientists have been committed to ecosystem properties to stabilize and increase community stability under climate change45.…”
mentioning
confidence: 99%
“…The frequent occurrence of rainfall extremes produces multiple disasters, including urban flooding, server soil erosion, landslides and debris flows [1]. Moreover, rainfall extremes affect the ecological process of the terrestrial ecosystem [2,3]. The spatial patterns of extreme precipitation trends exhibit heterogeneous characteristics, especially at a smaller scale, due to factors including warming, water vapor trends and topography differences [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that increased precipitation led to higher SWC (Gherardi & Sala, ), which increased nutrient (nitrogen) availability by promoting microbial processes (Brito et al, ; Guo et al, ; Sun et al, ) and ultimately enhanced plant growth (Plestenjak et al, ; Ye et al, ). However, in the present study, SWC did not increase with increased precipitation in June, August, and September.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that the desert‐grassland ecosystem carbon sink would be enhanced by increased precipitation and reduced by decreased precipitation by altering above‐ground biomass. This was a result of the increase in SWC due to increased precipitation (Gherardi & Sala, ), which improved the soil environment (Brito et al, ; Sun et al, ) and enhanced microorganism growth and development (Conant et al, ), and ultimately, affected carbon fluxes (Guo et al, ). Consequently, precipitation influenced carbon fluxes by altering SWC, species composition and biological growth.…”
Section: Discussionmentioning
confidence: 99%